ISLAMIC MICROECONOMICS IN ISLAMIC BOARDING SCHOOLS: FACING GLOBALIZATION CHALLENGES AND OPPORTUNITIES - Mundir, Ahmad (STKIP Pesisir Selatan, 2025)
This research examines the strategic role of Islamic boarding schools (pesantren) in implementing Islamic microeconomic principles amid globalization challenges and opportunities. Pesantren not only function as religious educational institutions but also possess significant potential as drivers of local economic development based on Islamic values such as justice, sustainability, and wealth distribution. This study highlights the integration of Sharia principles into pesantren economic practices through concepts such as productive waqf, Sharia-based cooperatives, and community empowerment. Main challenges include limited human resources, lack of access to capital, and the need for technological adaptation. However, globalization also offers opportunities through digitalization and increased public awareness of Islamic economics. By adopting maqāṣid al-sharīʿah theory, institutional economics, and social innovation, pesantren can develop sustainable, inclusive, and competitive economic models. This research recommends improving Islamic financial literacy, utilizing digital technology, and building strategic collaborations to support Islamic microeconomic development in pesantren environments.